Ta’thīr Istikhdām Wasīlah Sijjil al-Quṡāṡāt fī Taḥsīn Mahārah al- Kitābah - Jezy, Ahmad; Yusra, Oktarina; Rizal, Eka; Nurhasnah, Nurhasnah (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2024)
Arabic learning is divided into four skills, including writing skills. The researchers discovered that at Al-ishlah Islamic High School Bukittinggi, many students were making mistakes in writing letters, words, and even Arabic sentences. Additionally, there was a lack of engaging learning materials for developing writing skills. The objectives of this study are (1) To find out the steps for using Scrapbook media in learning students' writing skills at Al-Ishlah Islamic High School Bukittinggi. (2) To find out how much influence the use of Scrapbook media in improving the writing skills of students at Al-Ishlah Islamic High School Bukittinggi. Researchers use quantitative research methods with a Quasi-Experimental approach. The results of this study are (1) The steps for using Scrapbook media in learning writing skills consist of three stages, namely the preparation stage, the application stage, and the evaluation stage. (2) The amount of influence of using Scrapbook media in improving students' writing skills is 70.2%. Researchers concluded that the use of scrapbook media had a positive effect in improving the writing skills of tenth grade students of Al-Ishlah Islamic High School Bukittinggi.